Hydrodynamics of the melt in crystallizer at casting by frosting - E. I. Marukovich; V. F. Bevza; V. Ju. Stetsenko (Литьë и металлургия)
There is investigated the influence of hydrodynamic and thermalphysic characteristics of the liquid cast iron flows in crystallizer on formation of castings at continuously circular casting by frosting.